O Programa Mesa Educadora e as suas contribuições para a formação dos professores da Educação Infantil em São Caetano do Sul - Godeguez, Anelise Delgado (2016)
This research aimed to investigate the vision of beginning teachers about the contributions that the Program denominated Mesa Educadora for Early Childhood brought to the improvement of classroom practices and, specifically, about the area of mathematics. This program have a purpose of teachers professional development based on sharing experiences on everyday school life. An investigation was developed with a qualitative approach and used two methodological procedures: semi-structured interview with the coordinator of the program and with four early childhood education teachers from São Caetano do Sul (SP) program participants and analysis of program documents to identify the concepts, methodology and information of implementation to this program inside the city. The theoretical source is supported by the contributions of Imbernón (2010), Marcelo García and Vaillant (2011), Tardif (2010), Gatti (2013), Lima (2006), Campos (2002), Kishimoto (2002) Oliveira (2002). In this research, the coordinator and the teachers showed evidences of reflections about the successes and difficulties encountered in their practices at the beginning of the teaching career. It was found that the Program Mesa Educadora for Early Childhood enables the professional development of teachers, supporting them to overcome the deficiencies of their initial formation. It is confirmed that the coordinator of the program make a fundamental role in the process of breaking barriers and professional development